STIM2 drives Ca2+ oscillations through store‐operated Ca2+ entry caused by mild store depletion. (21st February 2013) - Thiel, Markus; Lis, Annette; Penner, Reinhold
Key points: Stromal cell‐interaction molecule (STIM) 2 senses Ca 2+ levels in the endoplasmic reticulum and activates Ca 2+ channels in the plasma membrane upon store depletion. Here we report that STIM2 is preferentially activated by low agonist concentrations that cause mild reductions in endoplasmic reticulum Ca 2+ levels. This shows that store‐operated Ca 2+ entry is regulated through signal strength, with weak stimuli activating STIM2 and strong stimuli engaging STIM1. The results help us to understand how receptor activation enables differential modulation of Ca 2+ entry over a range of agonist concentrations and levels of store depletion. Abstract Agonist‐induced Ca 2+ oscillations in many cell types are triggered by Ca 2+ release from intracellular stores and driven by store‐operated Ca 2+ entry. Stromal cell‐interaction molecule (STIM) 1 and STIM2 serve as endoplasmic reticulum Ca 2+ sensors that, upon store depletion, activate Ca 2+ release‐activated Ca 2+ channels (Orai1–3, CRACM1–3) in the plasma membrane. However, their relative roles in agonist‐mediated Ca 2+ oscillations remain ambiguous. Here we report that while both STIM1 and STIM2 contribute to store‐refilling during Ca 2+ oscillations in mast cells (RBL), T cells (Jurkat) and human embryonic kidney (HEK293) cells, they do so dependent on the level of store depletion. Molecular silencing of STIM2 by siRNA or inhibition by G418 suppresses store‐operated Ca 2+ entry and agonist‐mediated Ca 2+ oscillations at low levels of store depletion, without interfering with STIM1‐mediated signals induced by full store depletion. Thus, STIM2 is preferentially activated by low‐level physiological agonist concentrations that cause mild reductions in endoplasmic reticulum Ca 2+ levels. We conclude that with increasing agonist concentrations, store‐operated Ca 2+ entry is mediated initially by endogenous STIM2 and incrementally by STIM1, enabling differential modulation of Ca 2+ entry over a range of agonist concentrations and levels of store depletion.